Transformations of Labour through the Lens of Sex Work - Šori, Iztok | https://orcid.org/0000-0002-7594-5530; Hrženjak, Majda | https://orcid.org/0000-0003-1809-5450 (Taylor & Francis, 2026)
This volume engages with the question of how labour is transforming under late capitalism, and what insights the study of sex work offers into these transformations. Presenting case studies from the Global North, this book situates sex work within the frameworks of neoliberal governance, digitalization, platformization, and gig economy to examine how economic relations, labour practices, and activism are changing under these conditions. It demonstrates that sex work offers a powerful lens through which to understand the contradictions of contemporary labour regimes: autonomy bound up with precarity, visibility with surveillance, and agency with algorithmic control. The book highlights the mobility and agency of labouring subjectivities, showing how resistance often emerges through strategic engagement with the very structures produced by neoliberalism. While affirming the importance of legal recognition of sex work, the book contends that this alone is insufficient to disrupt the broader systems of exclusion and inequality experienced by sex workers and embedded in late capitalist economies. This book will be of interest to scholars and advanced readers engaged in debates on labour, sexuality, and political economy. It is particularly relevant to those working in critical labour studies, feminist theory, sociology, and socio-legal research, as well as to policymakers and activists concerned with labour rights and social justice.